ANALISA EKONOMI BIAYA OPERASIONAL PENGOLAHAN TANAH CARA TRADISIONAL DAN MEKANIS PADA BUDIDAYA PADI - Darnawi Darnawi; Sri Widarta; Susi Widiatmi (Universitas Sarjanawiyata Tamansiswa, 2018)
This study aimed to determine the amount of land processing costs in traditional ways compared to mechanical means, and analyze the differences which can then inform farmers to be able to make production cost efficiency. The study was conducted for six months (June - October 2017) in Sleman, Bantul and Kulon Progo regencies, namely farmer groups that process using hand tractors and those who still use animal power. The research method is to create a questionnaire for farmers / farmer groups that contain questions related to the costs for land processing. The variables studied were the duration of tillage / ha, the time of land processing activities (morning, afternoon, evening or night), the method of tillage, the per-hectare cost of tillage and the depth of tillage. The data obtained was analyzed using variance analysis Complete Random Design with a 5% error rate. The results of the research in the three districts found that the traditional cultivation of land per 1000 m2 of land area requires greater operational costs than the processing of mechanical means. And land processing per 1000 m2 of land area traditional methods require much more time than mechanical means.Key words: land processing, operational costs, traditional ways, mechanical ways.